Huisbeelden in de moderne Nederlandstalige poëzie - Kalla, Irena Barbara (Lage Landen Studies, 2012)
This book explores images of the house in Dutch-language poetry from the postwar period. On the one hand the archetypical notion of the house has always had an established place in poetry. It is connected to the meaning of house as a building, but even more so as an imaginative house or a home. On the other hand the house is a rich metaphorical concept that is often used for expressing poetical ideas. In a historical survey of modern Dutch-language poetry different images of the house are presented. The overview shows that the choice of certain metaphorical concepts is connected to literary and extra literary contexts, and to the poetical ideas of poets. Conceptual integration - blending theory - is used throughout this book as a theoretical frame. From this perspective poems are regarded as a complex blend, a network of connections which are constructed during the reading and interpreting processes. Finally, the book shows how metaphorical blends are integrated in concrete poems and which kind of house images result from this process.